Constructing irregular theology : bamboo and Minjung in East Asian perspective - Chung, Paul S., 1958- (Studies in Systematic Theology, 2009)
The project of constructing Asian irregular theology in East Asian perspective, based on life-word of Bamboo and social political reality of minjung, embraces Dr. Chung's cross-cultural existence as he develops his long-standing interest and expertise in Christian minjung theology in new ways with the image of bamboo as a symbol for the theological perspective of grass roots marginality. Using the ancient Chinese story "The Seven Sages of the Bamboo Grove," Dr. Chung engages with Christian eschatological discourse to support an aesthetical-utopian theological ethics that is opposed to an ethics concerned with legitimation of a socio-economic status quo. In addition, Dr. Chung's develops his deep commitment to the Lutheran theology of the cross and the suffering Christ through the Buddhist concept of dukkha (suffering) to create, in the end, a genuinely East Asian contextual theology